(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes in detail the basic principles of franchising, its various forms, advantages and disadvantages, as well as the role of the franchise system in international business. The franchise plays an important role in creating new business opportunities in Uzbekistan and contributes to economic growth. In particular, the franchise is seen as a convenient way of doing business for women. The article also analyzes legal and financial issues related to franchises, discusses issues of flexibility and competitiveness in market conditions. In fact, this includes the factors necessary for the successful operation of the franchisee.